Mapping Abjection: Dissecting Racial and Sexual Boundaries in Mark Gevisser’s Lost and Found in Johannesburg - Koekemoer, Christopher Wayne (Journal of Literary Studies)
This article details the deconstruction of social identity in Mark Gevisser’s memoir Lost and Found in Johannesburg. It does so by emphasising how the city’s design reflects racial and sexual segregation through the construction of borders and boundaries that are nonetheless nebulous and artificial. In Gevisser’s memoir, his recollections are interspersed with the narratives of other marginalised individuals and groups. I employ Julia Kristeva’s theory of abjection to understand how systems of exclusion function not only to exclude, but paradoxically, how they allow spaces of inclusion. I argue that the apartheid city can be read as a social body that can be analysed in a similar manner to how the individual subject distinguishes itself from others. The social body therefore creates subjective boundaries between racialised and sexualised others to maintain its sense of autonomy.